2017
DOI: 10.1017/s0950268817002230
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical characterization of human respiratory syncytial virus in South Korea between 2009 and 2014

Abstract: Respiratory syncytial virus (RSV) can cause serious respiratory infections, second only to influenza virus. In order to know RSV's genetic changes we examined 4028 respiratory specimens from local hospital outpatients in Gyeonggi Province, South Korea over six consecutive years by real-time one-step RT-PCR; 183 patients were positive for RSV infection. To investigate the specific distribution of RSV genotypes, we performed partial sequencing of the glycoprotein gene. Of the 131 RSV-A specimens sequenced, 61 (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 43 publications
(99 reference statements)
6
20
0
Order By: Relevance
“…Following the first reports of RSV-A ON1 in Canada [9] and Germany [14], genotype ON1 was detected in many other countries and regions [3, 13], including Asia [8, 1728], Africa [12, 2931], Europe [3239] and North and South America [4043]. In line with our results, several multi-season studies have previously reported ON1 to have rapidly replaced RSV-A non-ON1 genotypes [18, 19, 25, 28, 3033, 35, 3739, 4245]. Furthermore, ON1 has recently been reported to be the currently most prevalent RSV-A genotype worldwide [43].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Following the first reports of RSV-A ON1 in Canada [9] and Germany [14], genotype ON1 was detected in many other countries and regions [3, 13], including Asia [8, 1728], Africa [12, 2931], Europe [3239] and North and South America [4043]. In line with our results, several multi-season studies have previously reported ON1 to have rapidly replaced RSV-A non-ON1 genotypes [18, 19, 25, 28, 3033, 35, 3739, 4245]. Furthermore, ON1 has recently been reported to be the currently most prevalent RSV-A genotype worldwide [43].…”
Section: Discussionsupporting
confidence: 88%
“…Reports on the clinical disease severity of RSV-A ON1 compared to RSV-A non-ON1 genotypes are inconsistent and have thus far mainly been based on observations from inpatients [2]. Our investigation is one of only few studies describing RSV-A ON1 separately for children requiring outpatient primary care [25], and indicates similar disease severity for outpatients infected with RSV-A ON1 and those with RSV-A non-ON1 infections. Regarding inpatients, we also found a similar clinical severity of RSV-A genotypes in children admitted to a general PW.…”
Section: Discussionmentioning
confidence: 60%
“…Substitutions, insertions, deletions, duplications, stop codon usage change and frame shift mutation all involved in the variability of G gene and may be related to its escape from the protection of the host neutralizing antibodies. Our study showed that except for G gene, the mutation frequencies of other genes were higher in RSV-A than in RSV-B, which may be attributed by a wider prevalence of RSV-A 38 , 39 . The mutation frequency of the G gene of RSV-B was higher than that of RSV-A, which may suggested a broad antigenic diversity in RSV-B, and this result was consistent with the phenomenon that RSV-A reacted with all the antibodies, whereas RSV-B showed different epitope characteristics in G gene in previous study in the very early time 3 .…”
Section: Discussionmentioning
confidence: 53%
“…These groups, thought to have diverged about 350 years ago (Zlateva et al, 2005), have been observed to co-exist geographically and temporally with most outbreaks being dominated by RSV A and, in some locations, clear patterns of alternating dominance (White et al, 2005). Within the RSV groups are subgroups or genotypes whose frequency changes from season to season, with some genotypes undergoing complete replacement over time (Agoti et al, 2013, 2012; Park et al, 2017; Rodriguez-Fernandez et al, 2017; Song et al, 2017; Thongpan et al, 2017). This pattern of group and genotype replacement is thought to be due to a herd immunity effect (Botosso et al, 2009; Cane, 2001; Pretorius et al, 2013; White et al, 2005).…”
Section: Introductionmentioning
confidence: 99%